Sorption From Fundamentals to Applications - Kyzas, George Z. (IntechOpen, 2022)
The book presents a comprehensive overview of sorption, which is a multi-parametric separation process. It is extensively used in the removal of various pollutants from the tertiary stage of wastewater treatment, from leachates, etc. It discusses fundamental points of the technique as well as kinetic theories and isotherms. It also examines the synthesis and characterizations of all studied adsorbent materials to find their paths of sorption. Finally, it highlights the importance of having a cost-estimation plan for the synthesis of sorbent materials as well as predictions for their reusability.